2018
DOI: 10.24912/je.v20i3.405
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Komparasi Model Prediksi Financial Distress Altman, Springate, Grover Dan Ohlson Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2013

Abstract: This study purpose to determine the most accurate bankruptcy prediction model in order to suitable for use in its application to manufacturing companies in Indonesia, and to determine whether there is a difference Altman models with Springate models, Altman models with Grover models, and Altman models with Ohlson models. Scope of the study is limited to manufacturing industry companies listed on the Indonesia Stock Exchange during the years 2011-2013. This study comparing four bankruptcy prediction model by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
3
0
6
Order By: Relevance
“…In contrast, this research is not in line with research conducted by Putri (2016) which compares the Altman, Ohlson, and Zmijewski models in predicting electronic companies listed on the Tokyo Stock Exchange; and research conducted by Wulandari (2014) comparing Altman, Springate, Ohlson, Fulmer, Ca-Score, and Zmijewski models to food and beverage companies; each study found the prediction of Ohlson's model to be the most accurate model in predicting financial distress. Other research that does not support this research is a study conducted by Hastuti (2018) that compares the Altman, Ohlson, and Grover models in predicting financial distress in industrial manufacturing issuers and produces the most accurate research model is the Grover model.…”
Section: Table 4 Financial Distress Prediction Results -The Ohlson Mmentioning
confidence: 96%
“…In contrast, this research is not in line with research conducted by Putri (2016) which compares the Altman, Ohlson, and Zmijewski models in predicting electronic companies listed on the Tokyo Stock Exchange; and research conducted by Wulandari (2014) comparing Altman, Springate, Ohlson, Fulmer, Ca-Score, and Zmijewski models to food and beverage companies; each study found the prediction of Ohlson's model to be the most accurate model in predicting financial distress. Other research that does not support this research is a study conducted by Hastuti (2018) that compares the Altman, Ohlson, and Grover models in predicting financial distress in industrial manufacturing issuers and produces the most accurate research model is the Grover model.…”
Section: Table 4 Financial Distress Prediction Results -The Ohlson Mmentioning
confidence: 96%
“…Kebankrutan diartikan sebagai sesuatu yang legal atau sebagai peristiwa ekonomi yang ditandai dengan berakhirnya segala bentuk arus kegiatan perusahaan (Hastuti, 2015) (Hastuti, 2015). Analisis kebangkrutan dilakukan agar meminimalisir gejala-gejala kebangkrutan yang akan terjadi.…”
Section: Financial Distressunclassified
“…Model persamaan dari model Grover adalah sebagai berikut: G = 1,650X1 +3,404X3 -0,016ROA + 0,057 Dimana: X1= WCTA; X3 = EBITTA; ROA = NITA Kriteria untuk persamaan model grover adalah jika nilai G ≤ -0,02 maka bank dikategorikan mengalami kebangkrutan. Sedangkan nilai G ≥ 0,01 maka bank dikategorikan dalam kondisi sehat (Hastuti, 2015). Dengan model persamaan yang telah sesuai dalam pemilihan variabel dalam model kombinasi antara variabel makro dan mikro adalah sebagai berikut:…”
Section: Metode Analisis Model Groverunclassified
“…If G ≥ 0.01 then the company is included in the healthy category The accuracy test of the financial distress prediction model in this study uses the Type II error. The level of e error is known if the financial distress prediction model predicts that the research sample experiences distress, while the actual condition of the company does not experience financial distress or delisted [12]. The following is the formula for testing the accuracy of the financial distress prediction model and the Type II error: Research [13] states that the liquidity ratio in the financial distress prediction model has a positive effect on financial distress.…”
Section: Zmijewski Modelmentioning
confidence: 99%